Histone deacetylase 6 regulates the immunosuppressive properties of cancer-associated fibroblasts in breast cancer through the STAT3–COX2-dependent pathway. Issue 45 (8th November 2018) - Li, Ang; Chen, Ping; Leng, Ye; Kang, Jiuhong
Abstract Cancer-associated fibroblasts (CAFs) are important components in breast tumors and essential for tumor progression and metastasis. However, the role of epigenetic modification in driving the function of CAFs within breast tumors is only marginally known. Herein, we reported that histone deacetylase 6 (HDAC6), one of class II histone deacetylases, was frequently upregulated in the CAFs of breast tumor and promotes an immunosuppressive microenvironment. The genetic or pharmacologic disruption of HDAC6 in CAFs delays tumor growth, inhibits the tumor recruitment of myeloid-derived suppressor cells and regulatory T cells, alters the macrophage phenotype switch, and increases the CD8+ and CD4+ T-cell activation in vivo. Mechanistically, we identified prostaglandin E2/cyclooxygenase-2 (COX2) as a major target of HDAC6 in CAFs by regulating STAT3 activation. Overexpressing COX2 in HDAC6-knockdown CAFs can completely restore the immunosuppressive properties of the fibroblasts. Clinically, a positive correlation among the stromal expression levels of HDAC6, p-STAT3, and COX2 in human breast cancer was observed. High-stromal expression of HDAC6 was markedly associated with poor survival outcome. Overall, our findings indicated that fibroblastic HDAC6 was a vital epigenetic mediator involved in programming an immunosuppressive tumor microenvironment that dampens antitumor immunity. Thus, HDAC6 may be a good potential target to improve breast cancer immunotherapy.